2008
DOI: 10.1021/mp8000638
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Crystallization of Amorphous Nifedipine

Abstract: Amorphous solids are generally more soluble and faster dissolving than their crystalline counterparts, a property useful for delivering poorly soluble drugs. Amorphous drugs must be stable against crystallization, for crystallization negates their advantages. Recent studies found that crystal growth in amorphous indomethacin is orders of magnitude faster at the free surface than through the bulk and this surface-enhanced crystallization can be inhibited by an ultrathin coating. Herein, we report a second syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
157
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(172 citation statements)
references
References 19 publications
15
157
0
Order By: Relevance
“…The results show higher degrees of crystallinity on the surface of the compacts that in ground compacts both using Raman and XRPD, indicating that the higher crystallinity detected using Raman could be due to the crystallization itself being more pronounced on the compact surface. Crystallization on the surface of amorphous particles has been reported to be considerably faster than in the bulk using griseofluvin, indomethacin and nifedipine (Zhu et al, 2010(Zhu et al, , 2008Wu et al, 2007;Wu and Yu, 2006) due to surface molecules having a higher mobility than molecules in the bulk. Zhu et al (2010Zhu et al ( , 2008 and Wu et al (2007) showed that surface crystallization could be suppressed by coating the sample surface.…”
Section: Recrystallization Of Xylitol and Xylitol-silica Solid Dispermentioning
confidence: 99%
See 2 more Smart Citations
“…The results show higher degrees of crystallinity on the surface of the compacts that in ground compacts both using Raman and XRPD, indicating that the higher crystallinity detected using Raman could be due to the crystallization itself being more pronounced on the compact surface. Crystallization on the surface of amorphous particles has been reported to be considerably faster than in the bulk using griseofluvin, indomethacin and nifedipine (Zhu et al, 2010(Zhu et al, , 2008Wu et al, 2007;Wu and Yu, 2006) due to surface molecules having a higher mobility than molecules in the bulk. Zhu et al (2010Zhu et al ( , 2008 and Wu et al (2007) showed that surface crystallization could be suppressed by coating the sample surface.…”
Section: Recrystallization Of Xylitol and Xylitol-silica Solid Dispermentioning
confidence: 99%
“…Crystallization on the surface of amorphous particles has been reported to be considerably faster than in the bulk using griseofluvin, indomethacin and nifedipine (Zhu et al, 2010(Zhu et al, , 2008Wu et al, 2007;Wu and Yu, 2006) due to surface molecules having a higher mobility than molecules in the bulk. Zhu et al (2010Zhu et al ( , 2008 and Wu et al (2007) showed that surface crystallization could be suppressed by coating the sample surface. Nanubolu and Burley (2012) and Wu et al (2007) reported that the crystallization kinetics of amorphous drugs changed when covering the sample using a coverslip and thus restricting the surface molecule mobility.…”
Section: Recrystallization Of Xylitol and Xylitol-silica Solid Dispermentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have discovered that different modes of crystal growth can emerge as a liquid is cooled to form a glass (3)(4)(5)(6)(7)(8), causing crystal growth fronts to advance at velocities much faster than predicted by standard theories. One such growth mode [the glass-to-crystal (GC) mode] exists in the bulk and can cause an increase of crystal growth rate by a factor of 10 4 with a temperature drop by a few kelvin (3,4).…”
mentioning
confidence: 99%
“…One such growth mode [the glass-to-crystal (GC) mode] exists in the bulk and can cause an increase of crystal growth rate by a factor of 10 4 with a temperature drop by a few kelvin (3,4). Another new growth mode occurs at the free surface and can lead to much faster crystal growth than in the bulk (5)(6)(7)(8). Although these phenomena have been observed prominently in organic glasses, they may be relevant for understanding glass crystallization in general.…”
mentioning
confidence: 99%